Localized Corrosion of Nickel and Nickel-Molybdenum Alloys - Zamin, Mohammed (My University, 1976)
This investigation is concerned with the study of the localized corrosion of nickel and the effect of the addition of molybdenum on its corrosion properties. To this end, alloys containing up to 30 wt % Mo have been studied in 1N H₂SO₄ and chloride containing environments by potentiostatic and galvanostatic techniques and 'in-situ' microscopic observations.
The anodic oxidation of nickel has been studied by the galvanostatic technique. The experimental results have been used to develop the kinetic equation describing the film growth on nickel. It has been shown that an inverse, logarithmic behaviour is obtained in that the film growth current density is inversely proportional to the charge stored in the film. The resistivity of the film has been calculated and its value suggests that the film is pure and almost stoichiometric NiO.
The significance of the Flade potential of nickel in 1N H₂SO₄ solution is discussed in view of the results obtained and those existing in literature. The implications of the critical potential for determining the susceptibility to pitting corrosion of metals and alloys has been investigated for Ni and Ni-Mo alloys. It is concluded that the critical potential does not adequately describe the electrochemical conditions required for the pitting corrosion of Ni and Ni- Mo alloys in sulfuric acid solutions containing chloride ions.
The passive electrode has been treated as a metalsemiconductor system and justification has been provided for the assumption of a 100% efficiency for the current density during cathodic reduction.
The charge required to reduce the film formed on Ni and Ni-Mo alloys in 1N H₂SO₄ and in the presence of chloride ions is reported. Some information is provided on the nature of the film on the Ni-Mo alloys in chloride containing solutions. Studies are reported on the polarization behaviour of the Ni-Mo alloys in synthetic sea water and on the corrosion morphology obtained after 30 day immersion in synthetic sea water and an acidic chloride containing solution.
It is proposed that the improved resistance to corrosion of Ni-Mo alloys in naturally corroding systems is due to a sluggish anodic reaction imparted by a slow hydration of the metallic ions, while under anodic polarization in the presence of chloride ions it is due to the presence of a diffusion barrier film of MoO₃. The results obtained on the Ni-Mo alloys have been explained on the basis of a defect model for the passive film on the alloys.
Keywords: Materials Science and Engineering; Metallurgy; Materials Science and Engineering